A two-dimensional inverse heat conduction problem for simultaneous estimation of heat convection coefficient, fluid temperature and wall temperature on the inner wall of a pipeline. (May 2015) - Lu, T.; Han, W.W.; Jiang, P.X.; Zhu, Y.H.; Wu, J.; Liu, C.L.
Abstract: The thermal stress caused by thermal stratification in the pipelines of nuclear plants can easily induce thermal fatigue. Predicting the temperature fluctuations at the inner wall in the pipeline without destroying the integral structure of the pipeline is one way of preventing accidents and ensuring safe operation in nuclear plants. In this work, the conjugate gradient method (CGM) is applied to solve the two-dimensional inverse heat conduction problem (IHCP) with multi-variables, in order to estimate the unknown temperature fluctuations at the inner wall of a cross profile, the temperature fluctuations of the fluid near the inner wall, and the heat convection coefficient between fluid and the inner wall of the cross profile in the pressurizer surge line, based on experimental outer wall temperature measurements. The accuracy of the inverse algorithm is then examined by comparing the estimated outer wall temperatures with the experimental temperatures. The numerical results show that the inner wall temperature of the cross profile can be accurately estimated by using the inverse algorithm for the test case considered. Highlights: Inverse problem was used to estimate the third boundary condition on inner wall. Conjugate gradient method (CGM) was applied to solve the inverse problem. Heat convection coefficient, fluid and wall temperature could be estimated.